Peningkatan Kebugaran Jasmani Melalui Permainan Tradisional Pada Mata Pelajaran PJOK Kelas VII - Prayogi , Sanggit; Mayzufi Firdiansyah, Hervyn; Achson Aljaohari, Zheindan; Wibowo, Sapto; Yuan Prambudi, Dwialih (Universitas Hamzanwadi, 2024)
Physical education has goals that are not only in the development of the physical realm, but also through physical activities and sports are expected to be a means of developing aspects of health, physical fitness, reasoning and critical thinking skills, emotional stability, social skills, and moral behaviour. In class VII, the endurance component becomes one of the physical fitness materials. Endurance can be measured with standardised instruments. Teaching methods through traditional games are used as an effort to increase the level of endurance in students. In this study, the teaching method was used which was applied to students of SMP Negeri 2 Ponorogo class VII A with a total of 32 students. The instrument used for the purpose of measuring pretest and posttest results is the Pacer Test. The research method applied for this research is classroom action research. The PTK carried out includes the Pre-Cycle, Cycle I, and Cycle II stages showing an increase. This is indicated by an increase in the percentage of good categories from 12.5% to 18.75% and a decrease in the percentage of low categories from 53.125% to 25%. These results show that traditional games can improve student learning outcomes in physical education learning on the endurance component.